2005
DOI: 10.1089/hyb.2005.24.236
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal Antibodies to Ricin:In VitroInhibition of Toxicity and Utility as Diagnostic Reagents

Abstract: Monoclonal antibodies (MAbs) against ricin toxin (RT) and its subunits were produced in mice. The MAbs were initially selected based upon the ability to either bind ricin or the individual subunits in a solid-phase enzyme-linked immunosorbent assay (ELISA). Several candidates were selected for further evaluation, including their ability to inhibit ricin intoxication in vitro and their utility as immunodiagnostic reagents. Although their ability to capture antigen when bound to the solid phase was poor, some MA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 22 publications
2
13
0
Order By: Relevance
“…The development of an effective immunotherapy against ricin has proven surprisingly elusive, despite the fact that dozens of MAbs against RTA and RTB have been described over the past 2 decades (6,9,10,14,20,24). It is becoming apparent from the study of other toxins, notably botulinum and anthrax toxins, that the most effective antidotes will likely consist of oligoclonal combinations of high-affinity MAbs (or Fabs) capable of functioning cooperatively (23,28).…”
Section: Discussionmentioning
confidence: 99%
“…The development of an effective immunotherapy against ricin has proven surprisingly elusive, despite the fact that dozens of MAbs against RTA and RTB have been described over the past 2 decades (6,9,10,14,20,24). It is becoming apparent from the study of other toxins, notably botulinum and anthrax toxins, that the most effective antidotes will likely consist of oligoclonal combinations of high-affinity MAbs (or Fabs) capable of functioning cooperatively (23,28).…”
Section: Discussionmentioning
confidence: 99%
“…The A-chain has N-glycosidase enzymatic activity against ribosomal RNA, while the B-chain is a lectin that binds to galactosyl moieties on the cell surface. Antibodies elicited against either the ricin A (RTA) or B-chain can neutralize the toxin, although anti- bodies to the A-chain are superior in this respect [4,5]. The major human B-cell epitope for RTA has been identified by Castelletti et al [6] from cancer patients treated with a ricinconjugate immunotoxin, and lies within residues 161-175.…”
Section: Introductionmentioning
confidence: 99%
“…4), these four toxins could be fully differentiated under the reaction conditions used. We observed that Mab 9C3 enhanced N-glycosidase activities toward an artificial substrate, whereas antiricin Mabs have typically been shown to neutralize the toxicity of ricin toward whole cells or cell-free ribosomes [15,27]. Mab 9C3 may have acted as a specific noninhibitory solubilizing agent for the toxins.…”
Section: '-Rumentioning
confidence: 95%
“…Mouse monoclonal antibody 9C3 (Mab 9C3) was provided by Dr. Mark Dertzbaugh (U.S. Army Medical Research Institute of Infectious Diseases, Fort Detrick, MD) [15]. The antibody was affinity purified using an UltraLink Immobilized Protein A/G column according to the manufacturer's instructions (Pierce Biotechnology, Inc., Rockford, IL).…”
Section: Methodsmentioning
confidence: 99%